Cytokine levels of interleukin-2 and 7 amongst antiretroviral therapy success and failure HIV patients attending the University Teaching Hospital, Yaoundé, Cameroon - Ikomey, George Mondinde (Int J Biol Chem Sci, 2020)
BACKGROUND: Immune reconstitution complications (IRC) are a major problem faced by HIV treated patients world wide. Interleukin (IL)-2 and IL-7 play vital roles in peripheral T-cell homeostasis. Our study objective was to measure and compare the blood plasma levels of IL-2 and IL-7 amongst antiretroviral therapy (ART) patients attending the Yaoundé University Teaching Hospital, Cameroon. METHODS: We performed a cross-sectional study with 296 HIV positive patients enrolled between July 2017 and May 2018 at the Yaoundé University Teaching Hospital. IL-2, IL-7, T-cell profile counts and plasma viral load were measured on whole blood specimens. Data obtained were analyzed using Graph Pad Prism 5.0 and Epi info 7.0. Software. RESULTS: IL-2 and IL-7 plasma concentration levels were higher in patients with ART failure compared to ART success, with a mean SD of 19.4±8 and 17.1±6 pg /ml, 35.26±11 and 21.5±5 pg/ml, with p < 0.001 and < 0.001. There was a direct and significant correlation between viral load, IL-2 and IL-7 with p values = 0.028, and 0.020, respectively. There was an association between IL-2, IL-7 and viral load in relation to the duration on treatment (DT), with p values = 0.003 (R(2)=0.041, CI= 0.069 – 0.34) ,0.017 (R(2)=0.027, CI=−0.30 – 0.030), and 0.001 (R(2)=0.048, CI=−0.047–0.76). CONCLUSION: Considering that limited surrogate markers are availiable for monitoring immune reconstitution and high associated mortality rates, IL-2 and IL-7 could be a good immunological predictor for ART failure and success in HIV infected individuals.